2021
DOI: 10.3390/ma14081935
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Characterization of Porous Asphalt Mixtures with Aramid Fibers

Abstract: Recent studies have shown that fibers improve the performance of porous asphalt mixtures. In this study, the influence of four different fibers, (a) regular aramid fiber (RegAR), (b) aramid fiber with latex coating (ARLat), (c) aramid fiber with polyurethane coating (ARPoly), (d) aramid fiber of length 12 mm (AR12) was evaluated on abrasion resistance and toughness of the mixtures. The functional performance was estimated using permeability tests and the mechanical performance was evaluated using the Cantabro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The researchers noticed that the higher the content of fibers, the better the fracture toughness. Gupta et al [ 125 ] stated that reinforcing a porous asphalt mix with 12 mm long aramid fibers notably boosted the tensile strength, moisture resistance, and cracking resistance of the asphalt mix. Xing et al [ 126 ] confirmed that modifying bitumen with 2 mm long aramid fibers at a proportion of 2% by bitumen weight improved rheological and physical properties at high and low temperatures.…”
Section: Results and Analysismentioning
confidence: 99%
“…The researchers noticed that the higher the content of fibers, the better the fracture toughness. Gupta et al [ 125 ] stated that reinforcing a porous asphalt mix with 12 mm long aramid fibers notably boosted the tensile strength, moisture resistance, and cracking resistance of the asphalt mix. Xing et al [ 126 ] confirmed that modifying bitumen with 2 mm long aramid fibers at a proportion of 2% by bitumen weight improved rheological and physical properties at high and low temperatures.…”
Section: Results and Analysismentioning
confidence: 99%
“…It should be emphasized, though, that the addition of fibers has a limit on how much low-temperature strength in asphalt mixtures may be improved. Asphalt mixtures' moisture sensitivity can be increased by aramid fibers, while their mechanical qualities can be enhanced by ceramic fibers [3][4][5]. The low-temperature performance of asphalt mixtures can be enhanced by mixing polyester fiber with an anhydrous calcium sulfate whisker.…”
Section: Introductionmentioning
confidence: 99%
“…Fibers are commonly added to OGFC mixtures to increase durability; however, this has an impact on the interconnection of the air void distribution and permeability performance [10]. Anik Gupta et al [11] investigated the impact of different aramid fibers on the permeability and the study results showed slight permeability decreases, which might be due to fibers blocking some of the air voids in the mixes. The thickness of OGFC pavement layers has always been considered an important factor that may affect permeability in OGFC.…”
Section: Introductionmentioning
confidence: 99%